Lung Mesenchymal Stem Cells Ameliorate Elastase-Induced Damage in an Animal Model of Emphysema - Donato Cappetta; Antonella De Angelis; Giuseppe Spaziano; Gioia Tartaglione; Elena Piegari; Grazia Esposito; Loreta Pia Ciuffreda; Angela Liparulo; Manuela Sgambato; Teresa Palmira Russo; Francesco Rossi; Liberato Berrino; et al. (Stem Cells International)
Pulmonary emphysema is a respiratory condition characterized by alveolar destruction that leads to airflow limitation and reduced lung function. Although with extensive research, the pathophysiology of emphysema is poorly understood and effective treatments are still missing. Evidence suggests that mesenchymal stem cells (MSCs) possess the ability to engraft the injured tissues and induce repair via a paracrine effect. Thus, the aim of this study was to test the effects of the intratracheal administration of lung-derived mouse MSCs in a model of elastase-induced emphysema. Pulmonary function (static lung compliance) showed an increased stiffness induced by elastase, while morphometric findings (mean linear intercept and tissue/alveolar area) confirmed the severity of alveolar disruption. Contrarily, MSC administration partially restored lung elasticity and alveolar architecture. In the absence of evidence that MSCs acquired epithelial phenotype, we detected an increased proliferative activity of aquaporin 5- and surfactant protein C-positive lung cells, suggesting MSC-driven paracrine mechanisms. The data indicate the mediation of hepatocyte growth factor in amplifying MSC-driven tissue response after injury. Our study shed light on supportive properties of lung-derived MSCs, although the full identification of mechanisms orchestrated by MSCs and responsible for epithelial repair after injury is a critical aspect yet to be achieved.